1992
DOI: 10.1159/000186901
|View full text |Cite
|
Sign up to set email alerts
|

HBV Infection in Hemodialysis Patients: Monitoring and Prevention

Abstract: From 1986 to 91,174 dialysis patients were studied. The prevalence of previous HBV infection and of chronic carriers was 33.3 and 4.6%, respectively. Immunization rate after vaccination (3 doses) was 63%. In 1991, we proposed a vaccination with 4 doses and recommend a 6-monthly anti-HBs evaluation to assess the timing of any booster dose needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…As far as seroprotection rate is concerned, the seropro tection rate afforded by us after the third vaccine dose (67%) is in keeping with other studies which used a simi lar vaccine schedule [24][25][26], and it is lower than the response rates obtained by other investigators who used a larger amount of vaccine [12], Among the responders of our population, 57% (45/79) were high responders at month 4, which allowed the antibody response to persist: at month 24, 76%(39/51)ofpatientsavailablc forevalua tion maintained protective levels of anti-HBs, 46% (18/ 39) of them being high responders.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As far as seroprotection rate is concerned, the seropro tection rate afforded by us after the third vaccine dose (67%) is in keeping with other studies which used a simi lar vaccine schedule [24][25][26], and it is lower than the response rates obtained by other investigators who used a larger amount of vaccine [12], Among the responders of our population, 57% (45/79) were high responders at month 4, which allowed the antibody response to persist: at month 24, 76%(39/51)ofpatientsavailablc forevalua tion maintained protective levels of anti-HBs, 46% (18/ 39) of them being high responders.…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of previous HBV infection in HD subjects was 40%, such prevalence was 23 and 37%, respectively, in the Italian population [23] and in Italian HD subjects [24], In Japa nese HD patients it was 37% [4] and in HD subjects from the USA 50% [25], We did not observe any correlation between the prevalence of past HBV infection and the examined factors; the prevalence of persistent HBV infec tion is partially related only with the length of time on HD. The most likely explanation that can be put forward is a cohort effect, as periodic HBsAg testing and isolation of chronic HBsAg carriers were made mandatory over 10 years before this study in our unit.…”
Section: Discussionmentioning
confidence: 99%
“…Patients on maintenance hemodialysis represent a risk group for hepatitis virus infections and the prevalence of these infections is higher than in the general population [Theilmann et al, 1988;Carletti et al, 1992;Rivanera et al, 1993;Fabrizi et al, 1997;Sampietro et al, 1997;Sheng et al, 1998;Utsunomiya et al, 1999;Yuki et al, 1999]. This fact has been attributed to blood transfusions, especially in patients transfused before 1990 and to nosocomial transmission in dialysis units [Roll et al, 1995;Norder et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most common viral infections are caused by hepatotropic or other hepatitisassociated viruses such as hepatitis B virus (HBV) [Theilmann et al, 1988;Carletti et al, 1992] hepatitis C virus (HCV) [Rivanera et al, 1993;Fabrizi et al, 1997], GB virus C/hepatitis G virus (GBV-C/HGV) [Sampietro et al, 1997;Sheng et al, 1998] and TT virus (TTV) [Okamoto et al, 1998;Utsunomiya et al, 1999;Yuki et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…3 Several other studies have revealed increased incidence of hepatic functional derangements in Hepatitis B and C infection in the form of elevated ALT and AST levels in patients on hemodialysis. The present study was designed to examine the prevalence of Hepatitis B and Hepatitis C in relation to duration of dialysis, to study the seroconversion from negative to positive in patients on chronic hemodialysis and to find out the incidence of liver function derangements in patients with Hepatitis B and Hepatitis C.…”
Section: Introductionmentioning
confidence: 98%